Housing And Services For The Elderly: A Case Study In Jinhua Street Neighborhood In Guangzhou China - Lin Lin (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
This paper is the result of a research focuses on the elderly living in Jinhua Street in the city of Guangzhou, China. These elderly people are retirees who are women over 55 and men over 60 year of age. The paper will respond to some of the varied needs of the elderly. It is mainly concerned with the housing and services for the elder in the neighborhoods. China has the largest elderly population in the world which account for more than one